Immagini del mondo e strategie politiche. Lo spazio tra Foucault e Marx - Giroldo, Luigi (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
This article analyzes the Question on geography – an interview released by Foucault to the editorial staff of Hérodote – focusing especially on the meaning of space in Foucault’s thinking and on the comparison between Marx’s and Foucault’s works. The relation between space and power can be defined with the notion of strategy that becomes the central question of the debate, among Foucault and the editorial staff of Hérodote, on geography as knowledge (savoir).